CTIM-12. A PHASE 1 TRIAL OF IMMUNORADIOTHERAPY WITH THE IDO ENZYME INHIBITOR (BMS-986205) AND NIVOLUMAB IN PATIENTS WITH NEWLY DIAGNOSED MGMT PROMOTER UNMETHYLATED IDHwt GLIOBLASTOMA. (12th November 2021) - Lukas, Rimas; Sachdev, Sean; Kumthekar, Priya; Dixit, Karan; Grimm, Sean; Gondi, Vinai; Sharp, Laura; Lezon, Ray; James, David; Lesniak, Maciej; Stupp, Roger; Wainwright, Derek
Abstract: BACKGROUND: IDHwt glioblastoma with unmethylated MGMT gene promoter carries a poor prognosis. Preclinical studies have shown that combination of radiotherapy and dual immunotherapy with nivolumab and IDO inhibition significantly prolongs survival of mice with an orthotopic glioblastoma [Ladomersky, et al. CCR 2018;24(11):2559-2573]. In a clinical trial in patients with newly diagnosed glioblastoma with unmethylated MGMT we substituted temozolomide for dual immunotherapy combination. METHODS: Phase 1 trial [NCT04047706] using a 3 + 3 dose-escalation design. All received standard radiotherapy (30 x 2 Gy) with addition of once daily oral BMS-986205 and intravenous nivolumab (240mg every 2 weeks) begining on day 1 of radiotherapy and continuing until disease progression or intolerance. BMS-986205 dosing was increased from 50 mg to 100 mg. DLT period encompasses 6 weeks of radiotherapy and the 4 subsequent weeks. Immunocorrelatives being conducted before and after treatment include mass spectrometry for tryptophan and kynurenine levels, immunohistochemistry of resected tumor, and RNA-sequencing and flow cytometric analysis of PBMCs. RESULTS: Twelve patients were treated on 2 dose levels of BMS-986205 (50, 100 mg). Treatment-emergent toxicity was as expected for this population. Three (25%) treatment-related SAEs were reported. Dose limiting toxicity of grade 3 transaminase elevation was observed in 2 patients at the 100 mg dose level, while at lower doses of BMS-986205 no substantial alterations of liver enzymes was observed. No other relevant treatment related toxicity occured. Ongoing immunocorrelative profiling and preliminary outcome data (all patients minimal follow-up >12 months) will be available at the time of the meeting. CONCLUSIONS: Dose limiting toxicity of BMS-986205 in combination with nivolumab and radiotherapy is hepatic (reversible) transaminitis. The recommended dose for further investigation is 50 mg. Accrual is ongoing for the MGMT promoter methylated cohort using the same regimen without withholding temozolomide. A randomized phase 2/3 trial is approved within the NRG network.